2018
DOI: 10.3389/fmicb.2017.02628
|View full text |Cite
|
Sign up to set email alerts
|

Digital Image Analysis of Yeast Single Cells Growing in Two Different Oxygen Concentrations to Analyze the Population Growth and to Assist Individual-Based Modeling

Abstract: Nowadays control of the growth of Saccharomyces to obtain biomass or cellular wall components is crucial for specific industrial applications. The general aim of this contribution is to deal with experimental data obtained from yeast cells and from yeast cultures to attempt the integration of the two levels of information, individual and population, to progress in the control of yeast biotechnological processes by means of the overall analysis of this set of experimental data, and to assist in the improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Intermediate products including NADPH and monosaccharides generated during respiration process are utilized to synthesize lipids and polysaccharides with the consumption of ATP in anabolism. Studies have revealed that oxygen role in the production of energy storage products (lipids and polysaccharides) (Atashrouz et al 2018, Ginovart et al 2018. It indicates that oxygen is essential in the cell division and lipid accumulation of oleaginous microorganisms.…”
Section: Dissolved Oxygen Concentration Effect On Cell Growthmentioning
confidence: 99%
“…Intermediate products including NADPH and monosaccharides generated during respiration process are utilized to synthesize lipids and polysaccharides with the consumption of ATP in anabolism. Studies have revealed that oxygen role in the production of energy storage products (lipids and polysaccharides) (Atashrouz et al 2018, Ginovart et al 2018. It indicates that oxygen is essential in the cell division and lipid accumulation of oleaginous microorganisms.…”
Section: Dissolved Oxygen Concentration Effect On Cell Growthmentioning
confidence: 99%
“…The automated analysis of images facilitates the examination of microorganisms at specific times throughout a process, providing instantaneous information concerning the parameters assessed. Typically, automated image analysis is divided into three stages: image processing, variable acquisition and statistical analysis [12]. Automated analysis of yeast cell images is not a novel concept and is most commonly used to assess the number of cells suspended within media.…”
Section: Introductionmentioning
confidence: 99%
“…Observed cell heterogeneity may also be a result of disorders in the cell cycle of the analyzed strains after treatment with selected concentrations of pesticides [ 60 ]. In addition, the heterogeneity of cells to oxidative stress responses and increased levels of ROS can enhance the potential of interacting with DNA and cause genotoxicity leading to recombination and diverse mutations [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%